Aplicação de cobre em mudas cítricas - Tecchio, Marco Antonio [UNESP]; De Merlim, Tatiana Pires Almeida; Leonel, Sarita [UNESP]; Grassi Filho, Hélio [UNESP] (My University, 2015)
Seedling production in protected nursery is the basis of the São Paulo state citrus culture, and fertilization management is one of the main pitfalls in the process. Copper deficiency and excess in citrus seedlings have become a serious concern for seedling nursery owners. Based on these considerations, the study aimed at evaluating the effects of copper fertilization on citrus seedlings. The experiment was carried out at a commercial seedling nursery in Botucatu city/SP and consisted of 5 treatments: T1 – control, T2 – copper oxyfluoride (1.8 g L-1), T3 – cupric oxide (500 g L-1), T4 – copper chelate EDTA (0.04 mL L-1) and T5 – copper sulphate (2,5g L-1). After treatment allocation, monthly evaluations were performed for 5 months for mean plant height (cm), mean stem diameter (mm), above ground and root dry matter (g) and mean copper level in the leaves (mg kg-1) of the rootstocks of the rangpur lime (Citrus limonia, Osbeck) in the two first evaluations. The three following evaluations were performed in the “Valencia” orange cultivar (Citrus sinensis, Osbeck). The experiment was completely randomized with a split plot design, in which plots corresponded to treatments with copper fertilization, and subplots to months of evaluation. Mean values of copper were considered excessive, mostly in the products applied to the leaves.
Copper fertilization in citric seedlings
Keywords: Citrus limonia; Citrus sinensis; Coconut fiber; Growth